2020
DOI: 10.1097/md.0000000000022863
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of high TET1 expression in patients with solid tumors

Abstract: Background: Recently, increased expression of TET1 has been shown to inhibit tumor development in many studies. Therefore, a meta-analysis was conducted to assess the prognostic role of TET1 in solid tumors. Methods: PubMed, Embase, and the Web of Science (last updated on June 13, 2019) were searched and 16 eligible studies involving 3100 patients were eventually taken forward into the meta-analysis. Results: Pooled results indicated that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…In addition, it was found that reduced expression of TET1 is associated with poor prognosis of early breast cancer patients ( 20 ). This finding was supported also by a recet meta analysis and literature review ( 21 ). Moreover, another study showed cytoplasmic mislocalization of TET1 and thus decreased 5hmC levels correlates with poor prognosis especially in PR and ER negative breast cancer patients ( 22 ) Mechanistically, TET1 was shown to be antitumorigenic by regulating different targets.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, it was found that reduced expression of TET1 is associated with poor prognosis of early breast cancer patients ( 20 ). This finding was supported also by a recet meta analysis and literature review ( 21 ). Moreover, another study showed cytoplasmic mislocalization of TET1 and thus decreased 5hmC levels correlates with poor prognosis especially in PR and ER negative breast cancer patients ( 22 ) Mechanistically, TET1 was shown to be antitumorigenic by regulating different targets.…”
Section: Introductionsupporting
confidence: 62%
“…The role of TET1 in breast cancer is controversial. While some studies indicated that TET1 is a tumor suppressor gene ( 20 , 21 ), others demonstrated that it is an oncogene ( 16 , 32 ). In the current study our results indicate that the picture seems to be more complicated and that the role of TET1 in breast cancer is not black and white.…”
Section: Discussionmentioning
confidence: 99%
“…Q. Ke и соавт. показали, что высокий уровень экспрессии TET1 в опухолевой ткани тесно связан с лучшими показателями общей выживаемости у пациентов азиатской популяции с опухолями органов дыхания и молочной железы [113]. Снижение экспрессии ТЕТ1 характерно для карциномы эндометрия, но не для предраковых заболеваний, таких как гиперплазия эндометрия.…”
Section: нарушения экспрессии белковunclassified
“…Of note, TET1 promoter methylation was also detected in primary tumors for the same cancer types as the cancer cell lines, but less frequently than in cell lines, which emphasizes the importance of microenvironment and cellular context in the regulation of TET1. Furthermore, functionally, ectopic expression of TET1 catalytic domain in cancer cell lines reactivated silenced tumor-suppressor genes ( DLit2 , ZNF382 , HOXA9 , and DKK1 ) and significantly suppressed clonogenicity of cancer cells compared to the catalytically dead mutant [ 72 , 73 ]. These findings support a tumor-suppressive role for TET1 which is predominantly silenced by promoter methylation in cancer [ 72 ].…”
Section: Are Tet Enzymes Tumor-suppressors or Oncogenes?mentioning
confidence: 99%
“…In this analysis, there were four breast datasets, three of which were Asian breast datasets. However, in the pooled subgroup analysis, the non-Asian breast dataset, which showed the opposite association between TET1 and OS, was excluded and therefore the prognostic role of TET1 was only established in the Asian dataset [ 73 ]. Therefore, the prognostic value of this association between TET1 and overall survival might only hold true in the Asian dataset and should be cautiously inferred and interpreted in the context of other breast cancer datasets and subtypes.…”
Section: Are Tet Enzymes Tumor-suppressors or Oncogenes?mentioning
confidence: 99%